2016
DOI: 10.4018/ijaie.2016070103
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Musculoskeletal Disorders in Handicraft Sector

Abstract: This research review article made an attempt to review such issues pertaining to handicraft sector. It highlight/covers following aspects in detail: ergonomics interventions in handicraft industries, occupational risk factor, and musculoskeletal disorders. The literatures over a decade reported that ergonomics concepts are more applied in large-scale industries like steel plant, power plant, manufacturing plants, automotive sectors etc. rather than small-scale industries like handicraft. However, applying ergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…7 Results of a Literature review has shown that application of ergonomic principles was more evident in large scale industries rather and small scale industries still lag behind despite of the fact that small scale industries require more manual labor. 8 Similar results have been reported by Shakerian et al (2016) 9 in Iranian handicraft workers. They studied the impact of work place physical activity on musculoskeletal discomfort among handicraft workers.…”
Section: Discussionsupporting
confidence: 79%
“…7 Results of a Literature review has shown that application of ergonomic principles was more evident in large scale industries rather and small scale industries still lag behind despite of the fact that small scale industries require more manual labor. 8 Similar results have been reported by Shakerian et al (2016) 9 in Iranian handicraft workers. They studied the impact of work place physical activity on musculoskeletal discomfort among handicraft workers.…”
Section: Discussionsupporting
confidence: 79%
“…A review of literature suggests that job satisfaction is positively correlated to organizational commitment (Moynihan, Bosswell and Bondreau, 2000), productivity (Böckerman and Ilmakunnas, 2012) and job performance (Hira and Waqas, 2012). Further, researchers have found significant cross-sector differences in job satisfaction (Gupta and Pannu, 2013;Singh and Jain, 2005;Mulinge, 2000;Sokoya, 2000;Meena and Dangayach, 2012). Therefore, the study hypothesize that:…”
Section: Job Satisfactionmentioning
confidence: 89%